2018
DOI: 10.1089/sur.2017.076
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and Background for the World Health Organization Global Guidelines on the Prevention of Surgical Site Infection

Abstract: Surgical site infections remain an important topic of concern for surgeons in all specialties and are currently the focus of global health agencies for prevention. Because patients have numerous co-morbidities that increase the risks of surgical site infections, and because of the emergence of more resistant pathogens, it is necessary to revise and update guidelines to assist surgeons in the prevention of these infections. This article will summarize the most recent WHO Global Guidelines for the prevention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…SSIs were defined by the US Centers for Disease Control and Prevention definitions for surgical site-infection surveillance. 11 At the end of the intervention period, an infection-control nurse who was blinded to patient group recorded the clinical data of patients in both groups.…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSIs were defined by the US Centers for Disease Control and Prevention definitions for surgical site-infection surveillance. 11 At the end of the intervention period, an infection-control nurse who was blinded to patient group recorded the clinical data of patients in both groups.…”
Section: Study Descriptionmentioning
confidence: 99%
“…9 During the last few decades, several papers have been published on optimal AP, and in this regard international guidelines for surgical prophylaxis have been updated and propagated. 11 Despite this, studies have shown that optimal practice is not achieved in many hospitals, especially in developing countries. 12,13 The knowledge and attitudes of surgeons about appropriate SAP are important factors in the implementation of guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the WHO launched the first global guideline on the use of antibiotic prophylaxis to prevent SSI [ 55 ]. The guideline will have applicability in all countries and be especially welcomed in developing countries [ 56 , 57 ]. The selection and application of prophylactic antibiotics should be conducted according to medical characteristics including the type of surgical incision, the possibility of infection, the type of potential pathogens and the prophylactic effect of antibiotics [ 58 ].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Антибиотикопрофилактика. Профилактическое введение антибиотиков должно быть проведено до кожного разреза (оптимально: за 30 мин -1 ч до начала операции), а не интраоперационно после пережатия пуповины [21][22][23][24]. Это обусловлено тем, что оптимальная концентрация антибиотика в тканях и крови создается между 30-й и 60-й минутой после его внутривенного введения.…”
Section: методика проведения анестезии при операции кесарева сеченияunclassified